Bacillus cereus endocarditis in native aortic valve - Ngow, Harris Abdullah; Wan Khairina, Wan Mohd Nowalid (Springer Japan, 2012)
Bacillus cereus endocarditis is rare. It has been implicated in immunocompromised individuals, especially in intravenous drug users as well as in those with a cardiac prosthesis. The patient was a 31-year-old ex-intravenous drug addict with a past history of staphylococcal pulmonary valve endocarditis, who presented with symptoms of decompensated cardiac failure. Echocardiography showed severe aortic regurgitation with an oscillating vegetation seen on the right coronary cusp of the aortic valve. The blood cultures grew Bacillus cereus. We report this as a rare case of Bacillus cereus endocarditis affecting a native aortic valve